Older type 2 diabetic patients are more likely to achieve glycaemic and cardiovascular risk factors targets than younger patients: analysis of a primary care database. Issue 12 (30th September 2015) - Barrot‐de la Puente, J.; Mata‐Cases, M.; Franch‐Nadal, J.; Mundet‐Tudurí, X.; Casellas, A.; Fernandez‐Real, J. M.; Mauricio, D.
Summary: Background: Older subjects with type 2 diabetes mellitus (T2DM) have differential characteristics compared with middle‐aged or younger populations, and require tailored management of the disease. Aims: To evaluate how clinical characteristics, degree of control of glycaemia and cardiovascular risk factors, presence of chronic complications and treatments differ between older T2DM patients and younger adults. Methods: Cross‐sectional study using data from a population‐based electronic database. We retrieved data from 318, 020 patients ≥ 30 years diagnosed with T2DM, attended during 2011 in primary care centres in Catalonia, Spain. We performed descriptive and comparative analyses stratified by gender and age subgroups: ≤ 65, 66–75, 76–85 and >85 years. Results: Both men and women across older age subgroups (> 65 years) had longer diabetes duration than younger adults (8.0 vs. 5.6 in men and 8.4 vs. 6.9 years in women; p < 0.001), but better glycaemic control (mean glycated haemoglobin 7.1 vs. 7.7 in men and 7.1 vs. 7.4 in women; p < 0.001), and better combined control of different cardiovascular risk factors (p < 0.001). Moreover, older patients were more likely to achieve glycaemic targets irrespective of having cardiovascular disease. The use of oral antidiabetics decreased with increasing age, and insulin in monotherapy was more frequently prescribed among patients in the older age subgroups. Diabetes‐related complications were more frequent in men of all group ages. In the older age subgroups, patients of both sexes had a longer duration of T2DM but better glycaemic control. In this context, the prevalence of diabetic retinopathy decreased unexpectedly with increasing age. Conclusion: Control of glycaemia and cardiovascular risk factors was better among older T2DM patients. There is a need for prospective studies to quantify the weight of risk factors in each complication to adapt the therapeutic and care approaches in elderly people.